2021
DOI: 10.1080/07388551.2021.1968785
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cells for skeletal tissue engineering

Abstract: Here, we review the use of human pluripotent stem cells for skeletal tissue engineering. A number of approaches have been used for generating cartilage and bone from both human embryonic stem cells and induced pluripotent stem cells. These range from protocols relying on intrinsic cell interactions and signals from co-cultured cells to those attempting to recapitulate the series of steps occurring during mammalian skeletal development. The importance of generating authentic tissues rather than just differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 170 publications
(208 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that ESCs or hESC-derived MSCs in the presents of bioactive osteogenic agents (such as β-glycerophosphate, ascorbic acid, and dexamethasone) induce differentiation into the osteogenic lineage [29]. It should be noted that somatic mesoderm or ectomesenchymal cells are the primary sources for the formation of osteogenic lineage cells [30]. Therefore, in another strategy, ESCs may be used, in which they directly induce the formation of mesoderm (co-cultured with hepatic cells and also used as the conditioned medium of hepatic cells) via bypassing the EB.…”
Section: Human Embryonic Stem Cells (Hescs)mentioning
confidence: 99%
“…It has been reported that ESCs or hESC-derived MSCs in the presents of bioactive osteogenic agents (such as β-glycerophosphate, ascorbic acid, and dexamethasone) induce differentiation into the osteogenic lineage [29]. It should be noted that somatic mesoderm or ectomesenchymal cells are the primary sources for the formation of osteogenic lineage cells [30]. Therefore, in another strategy, ESCs may be used, in which they directly induce the formation of mesoderm (co-cultured with hepatic cells and also used as the conditioned medium of hepatic cells) via bypassing the EB.…”
Section: Human Embryonic Stem Cells (Hescs)mentioning
confidence: 99%
“…Valuable for regenerative medicine, understanding muscle development, and studying genetic muscle disorders Suitable for tissue engineering and exploring therapeutic interventions [27][28][29][30][31] traditional 2D cultures, 3D engineered muscle has the following advantages: longer incubation time, higher maturity, stronger mechanical properties, as well as the integration of nerves and blood vessels. Therefore, muscle tissue engineering has been applied for drug testing, disease modeling, software robot building, and other biomedical fields.…”
Section: Variable Differentiation Efficiency Genetic Modificationmentioning
confidence: 99%
“…Key options for cell sources in muscle tissue engineering mainly include primary cells from muscle biopsies, [15][16][17][18][19][20] muscle cell lines, [21][22][23][24][25][26] and stem cells derived from muscle cells. [27][28][29][30][31] The choice of cell source in muscle tissue engineering depends on the research objectives and the crucial factors, including the physiological relevance of the model, regenerative potential, convenience, and target applications. Each cell source brings distinct advantages, limitations, and applicability, as summarized in Table 1.…”
Section: Cell Sources For Muscle Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have proposed to use stem cells derived from embryonic stem cells or induced pluripotent stem cells (iPS cells) for regeneration of musculoskeletal tissues [35][36][37][38][39][40]. However, these cell types have distinct disadvantages, hence the clinical application of these cell types for regeneration of musculoskeletal tissues will most likely not be introduced in routine clinical practice in the foreseeable future (Table 2) [3,5,7,8].…”
Section: Potential Risk Of Inflammatory Reactionsmentioning
confidence: 99%